Hubungan Tingkat Kecemasan Dan Motivasi Berprestasi Terhadap Performa Atlet Senam PPLP Arcamanik - Rizki Nur Ramdan; Helmy Firmansyah; Yusup Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study analyzed the relationship between anxiety levels and achievement motivation on the performance of gymnastics athletes at the Arcamanik Student Sports Education and Training Center (PPLP). Psychological factors, including pre-competition anxiety and motivation, are recognized as influencing athletes' performance during competition. The study used a descriptive quantitative method with a correlational approach, involving 11 athletes selected by purposive sampling, aged over 12 years and experienced in official competitions. Data were collected through questionnaires using the Sport Competition Anxiety Test (SCAT) instrument, achievement motivation instrumentation, and performance assessments. Data analysis was performed using the Pearson correlation test using SPSS. The results showed that the correlation coefficient between anxiety and performance was r = 0.411 (p = 0.209), while between achievement motivation and performance was r = 0.576 (p = 0.064). Both had a moderate and positive relationship, although they did not reach statistical significance below the threshold of p < 0.05. These findings suggest a tendency that increased achievement motivation and managed anxiety can contribute to improved athlete performance, although the small sample size limits the generalizability of the results. Keywords: Anxiety, Achievement Motivation, Athletic Performance, PPLP, Gymnastics